How Related Multiscreening Could Positively Affect Advertising Outcomes. Issue 4 (2nd October 2017) - Segijn, Claire M.; Voorveld, Hilde A.M.; Smit, Edith G.
Abstract : The use of multiple screens, also known as multiscreening, is assumed to have detrimental consequences for advertising outcomes. However, many people are engaging in this form of media multitasking on a daily basis. Therefore, it is important to focus on how to improve the effectiveness of advertisements when multiscreening. The aim of this study is to examine a key facilitator of advertising effects when multiscreening, namely task relevance. In two separate experiments—an online study ( n = 280) and a laboratory ( n = 185) study—we showed that people who engage in related multiscreening have better brand memory and more positive brand attitudes than people who engage in unrelated multiscreening via attention and subsequent program involvement. The results of the current study contribute to our understanding of multiscreening and advertising effects by showing that multiscreening does not always have to be detrimental to advertising effects. Furthermore, this study is unique because it combines two methodological approaches of multiscreening research.